Effects of world oil price movement on macroeconomic performance in Saudi Arabia - Youssouf, Mbodou Ali (2019)
This study examines the impacts of oil price shocks on the macroeconomic performance of the Kingdom of Saudi Arabia. The method used in the analysis was autoregressive distributed lag (ARDL) model and fixed proportions theory of Leontief’s (1936) input-output analysis. Data were collected during a period from the year 1991 to the year 2016 from the World Bank. The ARDL approach assures the existence of a long-run relationship and the effect of world oil price movement on macroeconomic performance. The result revealed that interest rate and exchange rate have a significant negative effect on export analysis in the long run. The result further indicated that interest rate has a significant negative effect while gross domestic product has a significant positive effect on government revenue. Finally, the result showed that interest rate has a significant positive effect on employment. The second objective of this study is to investigate the use of the input-output models to assess the effect of oil price movement on export, government revenue, and employment. The result revealed that the world oil price movement has a significant effect on all sectors. The world oil price has reduced revenues, lowered export revenue, and decreased employment. The most affected sectors due to world oil movement are mining and quarrying, wholesale and retail trade, repairs, renting of machinery, and equipment. The least affected sectors are education, electricity, gas and water supply, post and telecommunications. The value added to these sectors is mainly through forward linkages, implying that the output of these sectors demands high oil price to contribute to economic growth. The implication of this research is the multiplier impact of negative oil shocks arising from depending on crude oil can be large. Thus, we recommend that policymakers implement policies that will diversify the economy and encourage the production of goods and services from other sectors.